Innovation: the paradox of back to the future - Pennings, Johannes (Henry Stewart Talks, 2011)
Three issues related to innovation in established companies, Innovation and change, "Paradigm Shift", Sustainable success, Building a better mousetrap, Examples from different products, The lesson of Icarus, When are small steps not so small, Continuous innovation, Market evolution, How to transition with the market, Old and new dominant designs, Change through stealth, Tools for moving back to the future, Ambidexterity, Open innovation, Lessons on innovation
Reviewed at 2018/08/30